Associations of serum adiponectin with markers of cardio-metabolic disease risk in Indigenous Australian adults with good health, diabetes and chronic kidney disease. - Hughes,JT; O'Dea,K; Piera,K; Barzi,F; Cass,A; Hoy,WE; MacIsaac,RJ; Maple-Brown,LJ (Obes Res Clin Pract, 2016)
UNLABELLED: The higher serum adiponectin concentrations observed in females are often attributed to differences in adiposity or sex hormones. There is little data describing adiponectin in Indigenous Australians, and no studies examining its association with cardio-metabolic disease risk markers and chronic kidney disease (CKD). AIM: To describe the relationship of serum adiponectin with cardio-metabolic disease risk markers and kidney function in a community-based sample of Indigenous Australian adults, with particular reference to sex-specific differences. METHODS: A cross-sectional analysis of a community-based volunteer sample of 548 Indigenous Australian adults (62% female), stratified into five cardio-metabolic risk groups ranging from good health (strata-1) to high cardio-metabolic risk and low measured glomerular filtration rate (mGFR, <60ml/min/1.73m2) (strata-5). We examined serum adiponectin concentrations with cardio-metabolic risk markers, albuminuria and mGFR. RESULTS: Indigenous Australian females had a lower than expected adiponectin concentration (3.5μg/ml), which was higher than males in strata 1-4 (as in other populations), but not in strata-5 (mGFR<60, p=0.19), and higher leptin: adiponectin ratio than other populations (7.8ng/μg - strata-1, healthy females; 12.2ng/μg - strata-3, females with diabetes and mGFR≥90). Female-gender, HDL-cholesterol (positive), mGFR and waist: hip ratio (WHR) (inverse) were independently associated with log-adiponectin when mGFR≥60; when mGFR<60, female-gender was associated with 0.27 units lower log-adiponectin. CONCLUSION: Female-gender was not associated with higher adiponectin concentrations in Indigenous Australians with mGFR<60ml/min/1.73m2. High WHR was frequent in both genders, and inversely associated with adiponectin. Longitudinal studies are needed to examine relationships of serum adiponectin, obesity and cardiovascular disease events in Indigenous Australians.